2015
DOI: 10.1093/hsw/hlv010
|View full text |Cite
|
Sign up to set email alerts
|

Caste- and Ethnicity-Based Inequalities in HIV/AIDS-Related Knowledge Gap: A Case of Nepal

Abstract: Caste- and ethnicity-based inequalities are major obstacles to achieving health equity. The authors investigated whether there is any association between caste- and ethnicity-based inequalities and HIV-related knowledge within caste and ethnic populations. They used the 2011 Nepal Demographic and Health Survey, a nationally represented cross-sectional study data set. The study sample consisted of 11,273 women between 15 and 49 years of age. Univariate and logistic regression models were used to examine the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate sociodemographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21). Accordingly, this study aimed to investigate trends and the associations between sociodemographic, behavioural and knowledge-based factors and HIV transmission among male intravenous drug users (IDUs) in the Pokhara valley, Nepal from 2003 to 2017.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate sociodemographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21). Accordingly, this study aimed to investigate trends and the associations between sociodemographic, behavioural and knowledge-based factors and HIV transmission among male intravenous drug users (IDUs) in the Pokhara valley, Nepal from 2003 to 2017.…”
Section: Introductionmentioning
confidence: 97%
“…This could indicate that sexual health education programs are not currently working as effectively as necessary. Caste and ethnicity also act as major determinants of overall health literacy and knowledge of preventative measures (21). Injecting drugs at any point within a year has been shown to be a risk factor for non-utilisation of HIV testing centres (22), meaning that the study population are less likely to access these HIV preventative measures than other at-risk groups.…”
Section: Introductionmentioning
confidence: 99%
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate socio-demographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21). Accordingly, this study aimed to investigate trends and the associations between sociodemographic, behavioural and knowledge-based factors and HIV transmission among male intravenous drug users (IDUs) in the Pokhara valley, Nepal from 2003 to 2017.…”
Section: Introductionmentioning
confidence: 97%
“…There has been previous descriptive research in the Kathmandu Valley in Nepal into key risk factors and prevalence trends (7)(8)(9)17), however, more detailed analytic approaches to investigate socio-demographic and behavioural factors are currently lacking for this setting. Previous behavioural studies have also shown that there are multiple risk factors that act as determinants for HIV and other sexually transmitted diseases within other areas of Nepal (10,11), such as social class and education level (21). Accordingly, this study aimed to investigate trends and the associations between socio-demographic, behavioural and knowledge-based factors and HIV transmission among male intravenous drug users (IDUs) in the Pokhara valley, Nepal from 2003 to 2017.…”
Section: Introductionmentioning
confidence: 97%
“…This could indicate that sexual health education programs are not currently working as effectively as necessary. Caste and ethnicity also act as major determinants of overall health literacy and knowledge of preventative measures (21).…”
Section: Introductionmentioning
confidence: 99%